Edukasi Cuci Tangan yang Benar sebagai Upaya Hidup Bersih dan Sehat pada Siswa di SD Negeri 2 Meurah Mulia Kabupaten, Aceh Utara - Muslim Amin; Debi Abellia (BADAN PENERBIT STIEPARI PRESS, 2025)
Clean and Healthy Living Behavior (CHLB) refers to health practices carried out consciously based on learning to promote individual and family health. One key component of CHLB is proper handwashing, a simple yet effective method for preventing infection. Handwashing helps mechanically remove dirt and microorganisms from the skin using soap and water. This community service project aimed to increase awareness of CHLB, particularly the importance of correct handwashing techniques among students at SD Negeri 2 Meurah Mulia. The objective was to assess the students' understanding of hand hygiene and evaluate the impact of health education on their behavior. A qualitative approach was used, gathering primary data through interviews and observations and secondary data through literature, journals, and case studies. Educational outreach was conducted using media such as PowerPoint presentations and videos to convey proper handwashing procedures. Initial observations revealed that most students had limited knowledge about the proper steps of handwashing and the critical moments to wash hands, such as before eating and after using the toilet. Many students washed their hands hastily and ineffectively. After the educational session, a significant improvement was noted. Students demonstrated a better understanding of correct handwashing techniques and showed more interest in practicing proper hygiene. Overall, this initiative successfully enhanced the students’ awareness and practice of clean and healthy living, particularly through the promotion of proper handwashing behavior in SD Negeri 2 Meurah Mulia, North Aceh Regency.